2020
DOI: 10.1002/ange.202010794
|View full text |Cite
|
Sign up to set email alerts
|

Carbid‐Dihydride: kohlenstoffhaltige Spezies identifiziert in der Ta4+‐vermittelten Methandehydrierung

Abstract: Die Produkte der Methandehydrierung von Ta4+ Clustern in der Gasphase werden mittels Infrarot Multipler‐Photonendissoziationsspektroskopie (IRMPD) in Verbindung mit quantenchemischen Rechnungen strukturell charakterisiert. Die erhaltenen Spektren von [4Ta,C,2H]+ offenbaren eine Dominanz von Schwingungsbanden einer H2Ta4C+ Carbid‐Dihydridstruktur gegenüber deren eines HTa4CH+ Carbin‐Hydrids, wie Untersuchungen verschiedener Isotopologe zweifelsfrei zeigen. Da die Dehydrierung von Methan durch Kationen M+ typisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Since the higher number of atoms leads to an increase in structural complexity, several structural isomers of the involved species must be considered. In our previous study, [12c] structures and energetics of the possible initial structural isomers have already been discussed in detail. It was found that carbyne hydride (HTa 4 CH + ) and carbide dihydride (H 2 Ta 4 C + ) isomers are favored over the carbene one.…”
Section: Resultsmentioning
confidence: 99%
“…Since the higher number of atoms leads to an increase in structural complexity, several structural isomers of the involved species must be considered. In our previous study, [12c] structures and energetics of the possible initial structural isomers have already been discussed in detail. It was found that carbyne hydride (HTa 4 CH + ) and carbide dihydride (H 2 Ta 4 C + ) isomers are favored over the carbene one.…”
Section: Resultsmentioning
confidence: 99%
“…Typical time-of-flight (TOF) mass spectra for the reactions of mass-selected Ta 4 + and Ta 4 O 1−5 + clusters with methane at room temperature are shown in Figure 1. It is noteworthy that the reaction systems of Ta 4 O 2−5 + are newly investigated while the reactivity of Ta 4 + and Ta 4 O + that had been previously reported by other research groups 42,43,45 was reexamined for comparison. Upon the interaction of bare Ta 4 + with 910 mPa CH 4 for about 1.5 ms in our ion funnel trap reactor, 49 the dehydrogenation reaction occurred to produce Ta 4 CH 2 + ions (1, Figure 1a1).…”
Section: Cluster Reactivitymentioning
confidence: 99%